Perempuan dalam Harapan Laki-Laki Jawa Melalui Lirik Lagu Ndarboy Genk: Analisis Semiotika - Fajri, Namira Choirani; Ardhana Riswari, Aninditya (Humanis; Vol 29 No 1 (2025)DO - 10.24843/JH.2025.v29.i01.p01, 2025)
Ndarboy Genk is a Javanese singer whose lyrics often feature women as “main characters”. The songs also include the relationship between men and women in the context of Javanese society, including stereotypes about men’s expectations of women. Therefore, this study aimed to review Javanese men’s expectations of women contained in Ndarboy Genk’s song lyrics. This study is qualitative and uses a semiotic analysis approach that also links the constructivist paradigm. Data collection techniques refer to literature studies through the interpretation process. The results show that Javanese men’s expectations of women still exist today. These expectations are composed of the concepts of Masak, Manak, and Macak, accepting men as they are, and being loyal, and devoted. Therefore, it can be concluded that Ndarboy Genk’s song lyrics still focus on Javanese men’s hopes and desires regarding domestic matters that seem to perpetuate the oral culture that women must submit and obey men.